Antioxidant activities from pulp, peel and seed of white [Hylocereus undatus (HAW.) Britton & Rose] and red flesh pitaya [Hylocereus polyrhizus (F.A.C. Weber) Britton & Rose] - Adnan, Liana (2012)
Consumption of fruits and vegetables is important in maintaining good health as being proven by many studies. Their functional qualities as natural antioxidant, antimicrobial and anticancer were the common interest among researchers. Best known for its betacyanin pigments, pitaya fruit gained a lot of attention recently in investigating its functional properties. Hence, this study was conducted to determine the bioactive compounds (total phenolic, betacyanin, ascorbic acid, flavonoids and tocopherols) and antioxidant activity [2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging,conjugated diene and ferric thiocyanate (FTC)] of pulp, peel and seed of white (Hylocereus undatus) and red flesh pitaya (H. polyrhizus). Evaluations of antioxidant activity were carried out against the samples that were extracted using ethanol, chloroform and hexane. The chemical profiling of the selected extracts were then determined using gas chromatography-mass spectrometry (GC-MS). Seed of white and red flesh pitaya gave significantly (p<0.05) higher amount of total phenolic compounds but the least in betacyanin and ascorbic acid content in comparison to the pulp and peel. All flavonoids (catechin, epicatechin, myricetin and quercetin) tested were present in peel and seed of both types of pitaya fruits except for kaempferol while only catechin was detected in both pulps. Antioxidant activity of ethanol extract from red flesh pitaya pulp was significantly (p<0.05) higher than that of white flesh as determined by all the three different methods of antioxidant determination. The ethanol, chloroform and hexane extracts of peel and seed gave the same trend between the white and red flesh pitaya. Hexane extracts of peel gave the highest free radical scavenging activity as compared to that of ethanol and chloroform. However, there is no significant difference among all the extracts as determined by conjugated diene and FTC assay methods. On the other hand, ethanol extracts of the red flesh pitaya seed exhibited the highest antioxidant activity in comparison to other extracts and the seed of white flesh pitaya. Based on their high antioxidant activities, hexane extracts of both white and red flesh pitaya peel and ethanol extract of red flesh pitaya seed were selected to undergo fractionation and GC-MS analysis. Various compounds such as tocopherols, squalene and phytosterols were revealed from the fractionated hexane extracts of both types of pitaya peel and ethanol extract of red seed. In conclusion, numerous antioxidants are present in all parts of white and red flesh pitaya. Their utilization and further study can be carried out especially on the peel and seed judging from their ability to act as antioxidant.